2008
DOI: 10.1111/j.1502-3885.2006.tb01115.x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of high-level glaciofluvial terraces and re-evaluation of the established soil stratigraphy for Early and Middle Pleistocene surfaces, central Yukon, Canada

Abstract: February): Investigation of high-level glaciofluvial terraces and re-evaluation of the established soil stratigraphy for Early and Middle Pleistocene surfaces, central Yukon, Canada. Boreas, Vol. 35, pp. 96 Á/105. Oslo. ISSN 0300-9483.Palaeosols developed on the highest Yukon River glaciofluvial terraces were investigated in order to reconstruct the Plio-Pleistocene evolution of the river valley beyond Late Pleistocene glacial limits. A record of at least two pre-Reid (/311 kyr) glaciations is chronicled by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The only notable difference is that vermiculite was present in at least minor amounts in almost all of our samples, unlike in the earlier work. The presence of kaolinite, mica, and smectite in the Yukon River terrace paleosols reported by Huscroft et al (2006) is also consistent with this study. The minimal occurrence of chlorite is expected, as primary chlorites are easily weatherable, and so would not be present in older soils (Wilson 1999).…”
Section: Clay Mineralogysupporting
confidence: 91%
See 1 more Smart Citation
“…The only notable difference is that vermiculite was present in at least minor amounts in almost all of our samples, unlike in the earlier work. The presence of kaolinite, mica, and smectite in the Yukon River terrace paleosols reported by Huscroft et al (2006) is also consistent with this study. The minimal occurrence of chlorite is expected, as primary chlorites are easily weatherable, and so would not be present in older soils (Wilson 1999).…”
Section: Clay Mineralogysupporting
confidence: 91%
“…Foscolos et al (1977) found that clay fractions of soils formed in Reid and McConnell glacial deposits contained kaolinite, illite, chlorite, vermiculite, and chloritic intergrades, whereas the pre-Reid soils contained kaolinite, illite, montmorillonite, and interstratified kaolinite-montmorillonite. In the only subsequent study, Huscroft et al (2006) reported that the clay mineralogy of Wounded Moose paleosols on high-level terraces along the Yukon River included kaolinite, mica, and smectite. The clay mineralogy and chemistry of Wounded Moose paleosols were interpreted as indicating that soil formation initially occurred in a warm and subhumid climate with grassland-shrub vegetation Á an environment favourable to the development of montmorillonite (Rutter et al 1978).…”
Section: Settingmentioning
confidence: 99%
“…* GENESIS OF UPLAND SOILS 589 and the presence of chlorite and its intergrades in the colluvium, but not in the residuum, suggest a complex history of weathering. Other researchers (Foscolos et al 1977;Huscroft et al 2006) have suggested that the presence of smectite in Pleistocene soils in the Yukon indicates weathering under temperate conditions during interglaciations prior to the Reid glaciation. Smectite in the residuum in this study may be a relict feature of warm interglaciations, having formed in situ or translocated from higher in the profile from highly weathered near-surface horizons that have subsequently been eroded.…”
Section: Soil Weathering and Evidence Of Paleopedogenesismentioning
confidence: 96%
“…Other researchers (Foscolos et al 1977;Huscroft et al 2006) have suggested that the presence of smectites in Pleistocene soils in the Yukon indicate weathering under temperate conditions during interglaciations prior to the penultimate glaciation. Smectites in the residuum in this study likewise may be a relict feature from warmer interglaciations, having formed in situ or translocated from higher in the profile.…”
Section: Soil Weathering and Evidence Of Paleo-pedogenesismentioning
confidence: 97%
“…Since these data were first reported, only one set of additional analyses has become available for Yukon soils. Huscroft et al (2006) Micromorphological analysis of Yukon relict paleosols has been used to infer environmental changes through time (Fox and Protz 1981;Tarnocai and Smith 1989;Tarnocai and Valentine 1989;Tarnocai et al 1993;Fox 1994). In thin section, Wounded (Tarnocai and Smith 1989).…”
Section: Soil Formation In Glaciated Low-elevation Landscapesmentioning
confidence: 99%